Canadian Printmakers' Showcase 1974. - Carleton University, Ottawa (Ottawa : Carleton University, 1974)
Ayot, Pierre ; Bain, Freda Guttman ; Béland, Luc ; Bergeron, Fernand ; Besant, Derek Michael ; Bettinville, Henri ; Beveridge, Karl ; Brandis, J. Brender à ; Brodie, Jim ; Carr, Don ; d'Amour, Maurice ; Davison, Betty ; Deitcher, Gloria ; Dickson, Jenifer ; Dobereiner, Wendy ; Finn, Christopher John ; Forcier, Denis ; Foster, Velma ; Gagnon, Elizabeth ; Game, Robert ; Genush, Luba ; Haisoch, Hubert ; Harris, Salmon ; Harvey, Donald ; Heller, Jules ; Hunt, Katharine ; Jones, Fran ; Jule, Walter ; Kahane, Anne ; Kahn, Anita ; Laing, William ; Lax, Tomas ; Leclair, Michel ; Linnsen, Ben ; Manarey, Thelma ; Manning, Jo ; May, Margaret ; Maycock, Bryan ; Morrissey-Clayton, Merijean ; Mueller, John ; Myers, Edna ; Nolte, Gunter ; Olon, Gary G. ; Osborne, Lyndal ; Parsons, Bruce ; Porter, Edward ; Pura, William ; Reid, Leslie ; Roberts, David ; Sawai, Noboru ; Schmidt, Marianna ; Shepherd, Reginald ; Silvester, Roger ; Sise, Tom ; Skalnik, Pavel ; Soonash, Mrs. ; St. George, Marie Elyse ; Svilza, Joseph ; Swartzman, Roslyn ; Vezina, Christiane ; Will, John ; Williams, Christopher
biografie
Canadian printmakers' Showcase 1974, Carleton University, Ottawa, 1974
boek